Hemodynamic changes under spinal anesthesia after elastic wrapping or pneumatic compression of lower limbs in elective cesarean section: A randomized control trial - Prajith, Krishnamoorthy Retnamma (J Anaesthesiol Clin Pharmacol, 2020)
BACKGROUND AND AIMS: In spite of adequate fluid loading and left lateral tilt, parturients develop hypotension under spinal anesthesia during cesarean section. Elastic crepe bandage (CB) or pneumatic compression device (PCD) can be utilized to prevent the pooling of blood in lower limbs and thereby it may reduce the incidence of hypotension in these patients. This study was formulated to analyze the hemodynamic effects of leg wrapping with elastic CB and PCD in parturients undergoing for cesarean section under anesthesia. MATERIAL AND METHODS: Ninety term obstetric patients posted for elective cesarean section under spinal anesthesia were randomized into 3 groups: Group 1 (control), Group 2 (CB), and Group 3 (PCD). All the parturients had their legs wrapped with an elastic bandage and pneumatic sleeve applied over it. In Group 1 (Control), patients had their legs wrapped with CB loosely and pneumatic sleeve also applied was switched on. In Group 2, patients the CB was applied by stretching the bandage (15 cm width and 4 m stretched length). The PCD was not switched on in this group. In Group 3, the legs were wrapped with the CB loosely. The pneumatic sleeve was applied over the bandage, and the machine was switched on with a preset pressure of 40–50 mmHg after spinal anesthesia. Incidence of maternal hypotension and ephedrine requirement to maintain systolic blood pressure, neonatal Apgar score were recorded. RESULTS: The incidence of hypotension was significantly lower in Group 2 and 3 than the control group. Similarly, the requirement of ephedrine was significantly high in control group compared to CB and PCD. The incidence of hypotension was lower in group CB than group PCD. Meantime to receive the first dose of ephedrine was significantly low in control (7.37 ± 4.94 min) as compared to CB (10 ± 2.8 min) and PCD (13.88 ± 9.23). CONCLUSION: Leg-wrapping with CB is cost-effective, non-invasive, non-pharmacological, and effective tool to reduce the incidence of hypotension after spinal anesthesia in a parturient.